2022
DOI: 10.3390/cancers14235857
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Correlates with More Aggressive Features in Thyroid Cancer

Abstract: Oxidative stress (OS) can have an impact in the pathogenesis and in the progression of thyroid cancer. We investigated the levels of reactive oxygen species (ROS) in 50 malignant and benign thyroid lesions and 41 normal tissues, and correlated them with the thyroid differentiation score-TDS and the clinico-pathologic features. NOX4 expression, GPx activity and the genetic pattern of tumors were evaluated. In malignant and benign lesions, ROS generation and NOX4 protein expression were higher than in normal tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Several studies have investigated the relationship between inflammation, oxidative stress, and thyroid cancer [ 34 36 ]. In particular, chronic inflammation is linked to oxidative stress, which can cause DNA damage and thus contribute to the accumulation of cancer-initiating genetic alterations in cells [ 35 ].…”
Section: Endocrine Axes and The Mediterranean Dietmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have investigated the relationship between inflammation, oxidative stress, and thyroid cancer [ 34 36 ]. In particular, chronic inflammation is linked to oxidative stress, which can cause DNA damage and thus contribute to the accumulation of cancer-initiating genetic alterations in cells [ 35 ].…”
Section: Endocrine Axes and The Mediterranean Dietmentioning
confidence: 99%
“…For instance, a recent study found out that the serum levels of malondialdehyde, a well-established marker for screening and monitoring the oxidation stress level, were significantly higher in 55 patients with differentiated thyroid cancer compared to the healthy subjects [ 34 ]. Another study investigated the levels of ROS in 50 malignant and benign thyroid lesions and 41 normal tissues and correlated them with the thyroid differentiation score and the clinic-pathologic features [ 36 ]. In both malignant and benign thyroid tissue, the production of ROS and expression of the NADPH oxidase 4 (NOX4), a significant source of ROS, playing an important role in tumor cell proliferation and apoptosis, were found to be higher than in healthy tissues [ 36 ].…”
Section: Endocrine Axes and The Mediterranean Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is a risk factor for thyroid cancer [20,26,27], and it correlates with more aggressive features because ROS may repress genes involved in thyroid differentiation [28]. The antioxidant protection system of undifferentiated thyroid stem cells may therefore be important to preserve their normal biology, regulating the balance between stemness maintenance and the activation of self-renewal and differentiation [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Healthy cells, thereby subjected to chronic oxidative stress, can be transformed into cancer cells, through the mechanism presented above. Tumor cell survival, proliferation, chemoresistance, radioresistance, invasion, angiogenesis and stem cell survival are caused in the same way [ 11 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%